Compliant control for wearable exoskeleton robot based on human inverse kinematics. (22nd November 2018) - Brahmi, Brahim; Saad, Maarouf; Brahmi, Abdelkrim; Luna, Cristobal Ochoa; Rahman, Mohammad Habibur
Rehabilitation robots are a new technology dedicated to the physiotherapy and assistance motion and has aroused great interest in the scientific community. These kinds of robots have shown a high potential in limiting the patient's disability, increasing its functional movements and helping him/her in daily living activities. This technology is still an emerging area and suffers from many challenges like compliance control and human–robot collaboration. The main challenge addressed in this research is to ensure that the exoskeleton robot provides an appropriate compliance control that allows it to interact perfectly with humans. This article investigates a new compliant control based on a second-order sliding mode with adaptive-gain incorporating time delay estimation. The control uses human inverse kinematics to complete active rehabilitation protocols for an exoskeleton robot with unknown dynamics and unforeseen disturbances. The stability analysis is formulated and demonstrated based on Lyapunov function. An experimental physiotherapy session with three healthy subjects was set up to test the effectiveness of the proposed control, using virtual reality environment.